IMPLEMENTASI KEBEBASAN PERS DI MNC MEDIA TERHADAP FRAMING PEMBERITAAN PASANGAN CALON GANJAR-MAHFUD MENJELANG PEMILIHAN UMUM 2024 - , Cut Salwa Alifia Zahra; Fitri Marsheila; Iqlima Ghaitsa Majida; Ardhana Ulfa Aziz (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2024)
This study aims to review and outline the implementation of press freedom by MNC Media in the framing of Ganjar Mahfud's news before the 2024 Election contestation. The research method used is qualitative methods with data collection techniques used are literature studies. As for analyzing the data collected was used by descriptive technique. The results showed that the practice of press freedom by media oligarchics (Hary Tanoesoedibjo - MNC Media) realized in the form of alignment can influence public perceptions by ignoring the proportion of news against all-time Presidential-Candidates by forwarding the 2024 Presidential Election. The contribution the author hopes for this study is that Bawaslu can act decisively to take a smart role watching every media act according to ketentuaan Law No. 32 2002 Concerning Broadcasting. In addition, KPU needs to work together with all broadcasting media to make service advertisements for elections that display the entire paslon disproportionately that must be displayed throughout the media as a balancing frequency the news which is thought to take alignment.